The role of oxygen vacancies on the microstructure development and on the electrical properties of SnO2-based varistors - Parra, R.; Aldao, C. M.; Varela, José Arana [UNESP]; Castro, M. S. (Springer, 2005)
Variations on the microstructure development and on the electrical properties of SnO2-based varistors are discussed on the basis of the oxygen vacancies created or annihilated by the presence of different additives. Electron paramagnetic resonance (EPR) analysis of sintered samples evidenced a substantial increase in the paramagnetic oxygen vacancies concentration when Nb2O5 is added to the SnO2 center dot Co3O4 system. on the other hand, the observed diminution in the concentration of such species after the addition of Fe2O3 indicates solid solution formation. The quantification of paramagnetic oxygen vacancies allowed to confirm the proposed substitutions taking place in the lattice during sintering. These findings are supported by scanning electron microscopy, by density measurements and by current density versus electric field curves. The characterization of secondary phases through EDS assisted SEM and TEM is also reported in this work.
Keywords: defects; electrical properties; microstructure; varistors; EPR